Nestlings - Cassidy, Nat, 1981- (Nightfire, Tor Publishing Group, 2023)
"Ana and Reid needed a lucky break. The horrifically complicated birth of their first child has left Ana paralyzed, bitter, and struggling: with mobility, with her relationship with Reid, with resentment for her baby. That's about to change with the words any New Yorker would love to hear--affordable housing lottery. They've won an apartment in the Deptford, one of Manhattan's most revered buildings with beautiful vistas of Central Park and stunning architecture. Reid dismisses disturbing events and Ana's deep unease and paranoia as the price of living in New York--people are odd--but he can't explain the needle-like bite marks on the baby."--